Inflation and The Subsequent Timing of The Chinese Stock Market - Hui Hong; Fergal O'Brien; James Ryan (Asian Academy of Management Journal of Accounting and Finance, 2014)
This paper examines market-timing strategies based on inflation in a sample of three stock market indices drawn from the Shanghai and the Shenzhen Stock Exchanges between February 2002 and May 2010. Specifically, this study investigates the effectiveness of market-timing activity and its stability over time when using inflation. Consistent with previous studies, the results reveal significantly strong information conveyed through inflation in helping investors earn profits in excess of a buy-and-hold strategy. The nature of the information and the subsequent importance of the corresponding market-timing activity change over time, providing new evidence of time-varying investment opportunities in the Chinese stock market. The results of this study imply that the Chinese stock market has predictable components that can be exploited using information on inflation. However, this practice might experience time variations in a real-time framework, which draws investors' attention to asset allocation under economic uncertainty.